A MODERNIDADE E O TEMA DA MULTIDÃO EM BAUDELAIRE E ELIOT: THE MODERNITY AND THE THEME OF THE CROWD IN BAUDELAIRE AND ELIOT - ALVES, Elis Regina Fernandes (2019)
RESUMO: Este trabalho analisa como Charles Baudelaire e T. S. Eliot entendem a modernidade e tematizam a multidão e os temas a ela relacionados em seus poemas. Como referencial teórico, utilizo os aportes de Gumbrecht (1998), Nunes (1993), Calinescu (1999), para abordagem da modernidade, e estudiosos de Baudelaire e Eliot, como Junqueira (2014), Unger (1961), Wilson (1967), Calasso (2012), Hamburger (2007), Friedrich (1991), Benjamin (1989), dentre outros. Conclui-se que os poetas encaram de modo diferente a multidão: em Baudelaire, há certa busca por comunhão entre a multidão, na qual os homens buscam se comunicar; enquanto em Eliot, a multidão é desoladora, os homens nela se veem apartados e incomunicáveis. PALAVRAS-CHAVE: Charles Baudelaire. T. S. Eliot. Modernidade. Multidão.        ABSTRACT: This paper analyzes how Charles Baudelaire and T. S. Eliot understand the modernity and thematize the crowd and the themes related to it in their poems. As theoretical reference, I use the contributions of Gumbrecht (1998), Nunes (1993), Calinescu (1999), to approach the modernity, and Baudelaire and Eliot scholars such as Junqueira (2014), Unger (1961), Wilson (1967), Calasso (2012), Hamburger (2007), Friedrich (1991), Benjamin (1989), among others. It is concluded that the poets face the crowd differently: in Baudelaire, there is a certain search for communion among the crowd, in which men seek to communicate, while in Eliot the crowd is desolating, the men in it are separated and incommunicable. KEYWORDS: Baudelaire. Eliot. Modernity. Crowd.